PERSESUAIAN SUBJEK-VERBA BAHASA BIAK DAN BAHASA TERNATE (SEBUAH KAJIAN DESKRIPTIF-KOMPARATIF) - Simin Althur (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2011)
ABSTRACT This article is a description-comparative subject-verb concord between Biak language (one of the AN languages in Papua) and Ternate language (one of NAN language) in North Maluku. It is estimated that the subject-verb agreement of Biak language and the Ternate language is linguistic evidence that a common feature of the “lingual-fossil”, not as a result of the influence due to the historical relations of the past. Thus this paper refused Biak language as the Austronesian. Biak language is a member of NAN languages (Papuan Phylum) that only gets the effect of AN languages, rather than vice versa. Previous classification which considers the Biak language is a Austronesian language is a misclassification. ABSTRAK Artikel ini adalah sebuah deskripsi-komparatif persesuaian subjek-verba antara bahasa Biak (salah satu bahasa AN di Papua) dan bahasa Ternate (salah satu bahasa NAN) di Maluku Utara. Diperkirakan persesuaian subjek-verba bahasa Biak dan bahasa Ternate adalah evidensi linguistik yang merupakan “fosil-lingual” ciri bersama keserumpunan, bukan sebagai pengaruh akibat adanya relasi historis masa silam. Dengan demikian tulisan ini menolak bahasa Biak sebgai bahasa Austronesia. Bahasa Biak adalah anggota kelompok bahasa-bahasa NAN (Filum Papua) yang hanya mendapat pengaruh dari bahasa AN, bukan sebaliknya. Klasifikasi sebelumnya yang menganggap bahasa Biak sebagai bahasa Austronesia adalah misklasifikasi.